BOOKLET DEVELOPED TO MAXIMIZE MATHEMATICS LEARNING - Syaifuddin, Ahmad; wijayanto, adi; patoni, achmad (The Elementary Journal, 2023)
Booklet media as a development product to learn mathematics independently in order to improve student learning outcomes. The research method used is Research and Development (R&D) using the ADDIE model with the One Group Pretest Postest Design approach. The results showed that: 1) three media expert validators, three linguist validators and three material expert validators by 85% with very valid categories. 2) 10 samples in the reliability test on chronbach's alpha table, namely 0.716>0.60 with specifications suitable for use and student response to the distribution of questionnaires 92.7% with practical and effective specifications in terms of appearance. 3) the application of booklet media was analyzed using pretest questions through a homogeneity test of 0.457>0.05 which means homogeneous and a reliability test of kolmogorov smirnov of 0.962>0.05 with normal distribution and can be applied in class 5. 4) measuring the effectiveness of booklet media development through paired sample t-test with spss, namely 0.00<0.05 so that there is an influence on the effectiveness of critical thinking.